Pelatihan Simulasi Untuk Program Nc dengan CAD/CAM Software Mastercam X5 Bagi Mahasiswa Jurusan Pendidikan Teknik Mesin Fakultas Teknik UNM - Adi Rukma Adi; A. Muhammad Irfan; Ashar Pramono Ashar; Djuanda Djuanda; Muhsin Z Muhsin (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
This activity on applying science and technology to the community aims to: (1) Increase student knowledge regarding NC/CNC. (2) Increase students' ability to create drawings according to the positions and axes in the NC/CNC coordinate system (3) Increase knowledge about software that is widely used in industry. The conditions and problems faced are: Students are not yet familiar with the MasterCam X5 Software. This problem becomes the basic reference for the need to carry out training. Competencies of Mechanical Engineering Education Department students who are prepared as teaching staff at the vocational school level. The curriculum structure contains NC/CNC machining courses which require a simulation program in the form of CAD/CAM software which can produce programs or G-code (CNC programming language), so that this training becomes a trigger or socialization of the use of MasterCam X5 software with CAD content which is software. to create a product design. The output of the activity is: Mastery of MasterCam X5 which results in increased student knowledge in terms of understanding the hierarchy of making NC/CNC programs